2003
DOI: 10.1111/1539-6975.00060
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Intra‐Industry Trade in Insurance Services

Abstract: In light of the growing significance of trade in financial services, and the emphasis placed on trade in financial services during the Uruguay round of trade negotiations, this article is the first study of the determinants of intra-industry trade (IIT) in insurance services. The article analyzes and measures the magnitude of IIT in insurance services for the United States. The empirical results of the determinants of IIT indicate that foreign direct investment in insurance services (FDI) is a significant cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 38 publications
6
25
0
1
Order By: Relevance
“…(4) Level of competition (Herfindahl index (HI)): In addition to the market liberalisation, this paper also incorporates a variable that accounts for the level of competition in the market. Ma and Pope 64 find that a more competitive non-life 55 Li et al (2003). 56 Browne et al (2000).…”
Section: Market Structure Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Level of competition (Herfindahl index (HI)): In addition to the market liberalisation, this paper also incorporates a variable that accounts for the level of competition in the market. Ma and Pope 64 find that a more competitive non-life 55 Li et al (2003). 56 Browne et al (2000).…”
Section: Market Structure Factorsmentioning
confidence: 99%
“…Outreville 76 has documented that governance factors can influence the choice of foreign affiliates' location by the largest insurance groups. 65 Li et al (2003). 66 Summing the squared market shares of individual insurers in each country and multiplying the result by 10,000 calculate the HI.…”
Section: Governance/legal Factorsmentioning
confidence: 99%
“…It is different from inter-industry trade in which a country could specialize in financial services and exports it in exchange for a different good or service for which it has no comparative advantage. Li et al (2003) have shown that there is a considerable amount of IIT in insurance services generated when the US financial institutions deal with foreign financial institutions.…”
Section: Comparative Advantage In Financial Servicesmentioning
confidence: 99%
“…The study by Moshirian (2001) demonstrated that one of the implications of the distinction between US bank foreign branches and US banks' foreign assets is that one can now see that US banks' international lending activities can be generated by US banks operating in the United States, rather than exclusively by their operation in the foreign market. The study by Li et al (2003) analyze intra-trade in insurance services using some specific hypotheses to measure the role of financial institutions in supplying various differentiated financial products. Moshirian and Bishop (1997) and Moshirian and Van der Laan (1998) analyse and model the determinants of banks' foreign assets using quarterly data.…”
Section: Theoretical Framework For a Model Of Banks' Foreign Assets Hmentioning
confidence: 99%